Optimization of the crystallinity of polypropylene/submicronic-talc composites: The role of filler ratio and cooling rate - A. Makhlouf; H. Satha; D. Frihi; S. Gherib; R. Seguela (eXPRESS Polymer Letters)
Micronic and submicronic mineral fillers recently appeared as efficient reinforcing agents for polyolefins in addition to the benefit of bypassing the exfoliation/dispersion problem encountered in the case of incorporation of nanoscopic fillers such as clay. Submicronic-talc, designated as μ-talc, belongs to this kind of new fillers. This work was aimed at searching to optimize the crystallinity ratio of isotactic polypropylene in the presence of μ-talc in relation to the filler ratio of the composites and the cooling rate from the melt. In order to highlight the efficiency of the μ-talc on the crystallization of polypropylene comparison has been made with PP composites containing conventional talc particles. The study has been carried out on samples having μ-talc weight fractions covering the range 3–30%. In the context of optimizing the crystallinity ratio of the polypropylene matrix in the composites, calorimetric experiments have been planned using a full factorial design. The results were statistically processed by analysis of the variance via mathematical models for predicting the crystallinity ratio in relation to the cooling rate and the filler ratio. Contour graphs have been plotted to determine the effect of each parameter on crystallinity. The cooling rate proved to have a significantly stronger influence on crystallinity than the type and content of filler.